TELEMEDICINE AND ELECTRONIC HEALTH RECORD IMPLEMENTATION IN RURAL AREA: A LITERATURE REVIEW - Alfiyyah, Arifah; Ayuningtyas, Dumilah; Rahmanto, Agus (UI Scholars Hub, 2022)
The Indonesian Minister of Health 2019 issued regulations regarding the implementation of telemedicine services between health service facilities. Telemedicine is aimed primarily at rural areas. This research aims to look at the quality of telemedicine-based services, which are documented in an electronic health record (EHR) with complete information. This research uses the narrative literature review method: Garuda journal channels, Google Scholar, IEEE Explorer, ProQuest, PubMed, Science Direct, and Scopus. With the input-output process approach, eight scientific articles were published on countries with telemedicine/telehealth policies in rural areas. The implementation of telemedicine has advantages and disadvantages depending on the things supported and the target users. It must have policies, infrastructure, financial resources, and human resources to use, maintain and develop telemedicine. Telemedicine will help the health service process by increasing the degree of public health in rural areas if it is used on a large scale. The completeness of the EHR seems to be lacking in terms of informed consent. Still, a quality EHR can make it easier for health workers to enforce the history, establish the diagnosis, and provide patient healthcare.